Society and 'Heaven and Hell'—The Interplay Between Social Structure and Theological Tradition During Early Calvinism. (3rd July 2017) - Zafirovski, Milan
ABSTRACT: The paper reexamines the Calvinist reformulation of the doctrine of predestination and its social underpinnings. It applies a sociological approach by exploring whether and to what extent social, especially class, structure affected the Calvinist version of the doctrine of predestination. This application is based on the sociological premise that theologies, religions, and other beliefs originate within certain social settings, as well as influence the latter. The paper therefore represents an exercise in the sociology of theology and religion by analyzing the interplay between social structure and theological tradition in the form of the doctrine of predestination. It does so by investigating the interrelations between social forces and theological doctrine in the process of emergence and expansion of Calvinism as a predestinarian theology and religion as well as a radical political movement. It aims to contribute to a better understanding of the social conditions and effects of theology and religion in general, and of Calvinism in particular.